LiS: An AI for reviewing user service letters using plain language - de L. C. Felix, Adelnei; Lopes Pessoa, A. Carolina (Conference on Digital Government Research, 2025)
Digital transformation is a consolidated topic on government agendas and the use of AI-Artificial Intelligence in this context is increasingly expanding. However, efforts are needed to ensure that the digital transformation of public services no longer creates a channel for social exclusion. A key component in this sense is the use of clear language in products and information for access to digital public services. The main objective of this work is to describe the experience report of the construction of an Artificial Intelligence-AI, called LiS, with the purpose of improving the quality of the contents of service letters to users, from bodies of a subnational entity in Brazil. We will present the stages of developing the LiS, to review the contents of service letters to users, using plain language writing techniques. The combination of an automatic review, using LiS and a manual step, in the process of preparing and reviewing service letters for users, presented significant results in the services, which had their contents reviewed in this process. This gain was observed from the analysis of the results of evaluations of the content of services accessed by citizens. Another significant result presented was the reduction in review time for service letters. The use of the AI tool balanced with a human review stage, in the context of building and reviewing service letters for users, demonstrates efficiency in this process. Additionally, this combination reflects an approach to increase inclusion in citizen access to public services.